Clinical Characterization and Molecular Analysis of Fourteen Chinese Patients with Factor V Deficiency - Zhang, Ke; Ye, Longying; Jin, Yanhui; Chen, Yuan; Zeng, Manlin; Jia, Kaiqi; Yang, Lihong; Wang, Mingshan (Hämostaseologie, 2023)
Introduction Coagulation factor V (FV) functions as a vital cofactor that performs procoagulant roles in the coagulation system. We investigated 14 unrelated patients whose plasma FV levels were all below the reference range.Methods FV activity (FV:C) and FV antigen were detected by one-stage clotting and ELISA, respectively. All 25 exons of the F5 gene in patients were amplified by the PCR, and they were sequenced directly. Haplotype analysis was performed with different polymorphisms on F5. Protein modeling was applied to analyze the potential molecular mechanisms.Results Of five patients with higher FV levels (FV:C > 10%), only one had minor bleeding symptoms. In contrast, of the remaining eight patients with lower FV levels (FV:C < 10%), six showed various bleeding manifestations. A total of 10 mutations were detected from 14 patients (6 were novel mutations). Interestingly, the homozygous p.Phe190Ser was found in five pedigrees, and haplotype analysis showed that they shared almost the same haplotype, indicating the common origin rather than a hotspot mutation. In silico analysis preliminarily investigated the potential pathogenic mechanism of the mutation. Modeling analysis showed that all six missense mutations would lead to conformational alterations in the FV protein. Among them, three (p.Gly1715Ser, p.Ser1753Arg, and p.Asp68His) would decrease hydrogen bonds.Conclusion This is the largest genetic analysis of a single cohort of FV deficiency in Chinese. The study demonstrated that FV levels tended to be correlated with the probability of hemorrhage. The identification of a large number of unique FV-deficient pedigrees highlighted the screening for mutations in F5.
Keywords: factor V deficiency; sequencing; mutation profile; haplotype; hemorrhage